Public Service Mall as Local Governance Innovation in a Frontier Region: Evidence From the First One-Stop Shop in Papua, Indonesia - Yakobus Richard Murafer; Terianus Luther Safkaur; Eduard Metusala Johanis Kocu; Jackson Yumame; Melpayanty Sinaga; Ivana De Jesus (Bulletin of Social Studies and Community Development, 2026)
The distribution of Indonesia's Public Service Mall (Mal Pelayanan Publik, MPP) has been found to be uneven, with a higher concentration of these facilities observed in the more affluent western regions of the country. This study examines the Jayapura City MPP, inaugurated in May 2023 as the first MPP in the Land of Papua, and asks how the innovation was constituted, how the participation of its twenty-one institutions is formally designed, and what sustains and constrains it. A qualitative instrumental single-case design is utilized, drawing on nine core policy documents for 2022–2024 and national statistics to 2025. The corpus, which consists of regulatory instruments rather than accounts given by actors, is analyzed as institutional design analysis confined to rules in form. Constructs presupposing access to actors are excluded rather than inferred. The documentation reveals that approximately one hundred services have been consolidated in one location, but it appears this was achieved through co-location rather than integration. There is an absence of inter-agency data interoperability, and the one independent field study reports its absence in practice. The deficit is clearly defined in the rules as they are written. It is evident that a mayoral regulation lacks the authority to impose binding obligations on the four central vertical agencies that provide essential services to citizens. Furthermore, the existing cooperation agreements conspicuously fail to stipulate enforceable service standards, sanctions, dispute mechanisms, or review schedules. Consequently, participation depends on ongoing consent. A pre-specified search did not yield a published measurement of performance; relative advantage is asserted by adopters and measured privately, if at all, and no claim is made that citizens have obtained it. The hypothesis is that continuity is contingent on documented executive sponsorship and central supervision, rather than fiscal capacity. This proposition is advanced for comparative testing. The study posits that legal consolidation, asset tenure, digitalization, and the publication of performance data should be given due consideration.Keywords: Public service mall, One-stop shop, Governance innovation, Institutional design, Papua.